Study on Lubrication and Friction Reduction Properties of ZIF-8 Nanoparticles as Si3N4 Ceramic Water Lubrication Additives - Sui, Tianyi; Li, Lichao; Lin, Bin; Zhang, Yuhang; Zhang, Benyang; Yan, Shuai (Frontiers in Chemistry, 2021)
Ceramics can achieve superlubricity under water lubrication; however, their running-in period is long and application is rather limited by wear limit. Thus, zeolite imidazole ester skeleton (ZIF), an important branch of metal organic framework materials (MOFs), is expected to improve the tribological properties of lubricants and associated additives. As such, it has broad application prospects within the field. In this paper, ZIF-8 nanoparticles of varying concentrations were prepared and linked with amino functional groups. Specimens were used in silicon nitride self-matching pairs and their tribological properties were observed. After the experiment, friction surfaces were analyzed by scanning electron microscope (SEM), energy dispersive spectrometer (EDS), and Fourier transform infrared radiation (FTIR). The experimental results have shown that ZIF-8 nanoparticles greatly reduced both friction and wear. Comprehensively considering running-in time, average COF during the whole process and smooth friction period COF, optimal performance was obtained for the ZIF-8 nanoparticle solution concentration of 1wt%. Furthermore, it was concluded that the lubrication properties of amino-modified ZIF-8 nanoparticles are significantly better compared to that of the unmodified ZIF-8. The anti-friction mechanism of ZIF-8 as a ceramic water lubrication additive was mainly through the filling and forming of nanoparticle film on the ceramic surface.